The vanishing procyclicality of labor productivity - Jordi Galí; Thijs van Rens (Institute for the Study of Labor (IZA), 2010)
We document three changes in postwar US macroeconomic dynamics: (i) the procyclicality of labor productivity has vanished, (ii) the relative volatility of employment has risen, and (iii) the relative (and absolute) volatility of the real wage has risen. We propose an explanation for all three changes that is based on a common source: a decline in labor market frictions. We develop a simple model with labor market frictions, variable effort, and endogenous wage rigidities to illustrate the mechanisms underlying our explanation. We show that the reduction in frictions may also have contributed to the observed decline in output volatility.
urn:nbn:de:101:1-201008118088
Keywords: E24; E32; 330; labor hoarding; labor market frictions; wage rigidities; effort choice